PENGARUH LINGKUNGAN KELUARGA DAN TEMAN SEBAYA TERHADAP MINAT MELANJUTKAN STUDI S2 PADA MAHASISWA S1 PENDIDIKAN EKONOMI FKIP UNTAN - Rezka Yulianty Ananda; Junaidi H. Matsum; Syamsuri Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the effect of family environment and peer environment on interest in continuing graduate studies in undergraduate students of Economic Education FKIP Untan. This study uses a quantitative approach with an associative type of research. The population in this study were undergraduate students of Economics Education Regular FKIP Untan class of 2019, 2020, and 2021 totaling 106 people. The results showed that: (1) There is no significant effect of family environment on the interest in continuing graduate studies as indicated by a significance value of 0.884 and a calculated t value of -0.147, (2) There is a significant effect of peer environment on interest in continuing graduate studies as indicated by a significance value of 0.012 and a calculated t value of 2.562 with an influence of 6.4%, (3) There is a significant effect of family environment and peer environment together on the interest in continuing graduate studies, indicated by a significance value of 0.041 and the value of F count 3.323 with an influence of 5.3%.